Winter surface air temperature variation over Pakistan during 1970–2014 and its principal drivers in the tropical ocean. (January 2023) - Karim, Rizwan; Tan, Guirong; Ayugi, Brian; Ahmed Alriah, Mohamed Abdallah; Ngoma, Hamida
Abstract: This study examined the leading modes of Dec–Feb (DJF) month's surface temperature (DJFTs) and associated mechanisms of the most significant drivers affecting temperature variability during the season from 1970 to 2014. EOF1 of DJF temperature reveals uniform spatial patterns over most of Pakistan, except extreme north, accounting for 84.38% of the total variance. The typical warm (cold) years were 1970, 1981, 1988, 1990, 1993, 2004, 2006, 2009, 2010 (1972, 1974, 1975, 1984, 2008, 2012). Favorable atmospheric conditions for warm temperature events (DJFTs) in Pakistan is an anomalous anticyclone spread over northeast Pakistan to Tibet at low to upper levels. This condition is controlled by the south and western part, of which there are significant southerly and convergent flows at low level with ascending motion over the study area. Further, examination revealed a close relationship of warm DJFTs with Western Indian Ocean warming and Eastern Indian Ocean indices but insignificant relation with the Nino3.4 index. Ocean warming related to Dipole Mode Index over eastern Indian Ocean (DMIE) is more influential (r = 0.51) than over the western Indian Ocean (DMIW) index (r = 0.37). The Ocean warming related to DMIE (EIOW), especially in Nov-Dec-Jan (NDJ) season, forced a significant ascending motion locally and then induced warm DJFTs-associated circulation pattern, propagating northward to Europe. By the dynamic diagnosis, the adiabatic and diabatic heating for the warm DJFTs is not remarkable. However, the horizontal temperature advection is positive and significant over most parts of Pakistan, both in the DJF and NDJ season, from the surface to the top of the troposphere. It suggests that the warm temperature advection is the possible prominent way of the EIOW on the warm DJFTs. Highlights: Prominent low level anticyclone over northeast of study area with convergent southerlies and ascending motion over country favoured warm events of winter temperatures (DJFTs).Favorable atmospheric conditions during warm winters (DJFTs) in Pakistan are linked to anticyclone over northeast of region at low to upper levels with convergent southerlies and ascending motion over the study area. Ascending motion induced by Eastern Indian Ocean warming is propagated northwards across target region and further. Horizontal warm temperature advection has possible influence on warm events of DJFTs.